Psychological Elements of Insurgents Strategies of Al-Shabaab in Kenya and Boko Haram in Nigeria (Journal of Management and Social Sciences, 2024)
This paper examines the recurring activities of insurgents that have been at the core of security crises in Nigeria and Kenya arising from the activities of the Boko Haram (BH) and the Al-Shabaab adopting terrorist strategies and tactics. Data are generated from primary source through in-depth interviews with selected key informants and secondary sources with the review of relevant textbooks, journal articles, internet and other archival materials. The paper adopts content analysis of relevant literature and comparative analysis of the psychological elements of BH and Al-Shabaab groups in Nigeria and Kenya. It shows that insurgent activities have been a fundamental problem in Nigeria and Kenya in the last decade. The study identifies two psychological perspectives of insurgency - “syndrome” and “tool”. The paper also shows that, intimidation, chaos, provocation, attrition, virtual and cyberspace elements of terrorism strategies are common to Boko Haram and Al-Shabaab operations in Nigeria and Kenya. The paper concludes that individual African societies and the continent must address the syndrome factors to be able to combat terrorism as a tool in the hands of individuals and groups who disagree with states and see terrorism as an instrument to fight against perceived and/or real psychological trauma.